2018
DOI: 10.1007/s10616-018-0187-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of in vitro cytotoxic and genotoxic activities of some trimethoprim conjugates

Abstract: Trimethoprim, a commonly used antibacterial agent, is widely applied in the treatment of variety of infections in human. A few studies have demonstrated an extensive exposure of man to antibiotics, but there is still a lack of data for cytotoxic effects including nephrotoxicity, gastrointestinal toxicity, hematotoxicity, neurotoxicity and ototoxicity. The main purpose behind this study was to determine cytotoxic and genotoxic activities of trimethoprim (1), trimethoprim with maleic acid (2) and trimethoprim in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Indeed, our in vitro study showed that a high dose of TMP could also inhibit VEGF mRNA expression (Figure S1). High doses of TMP can induce cell toxicity [20], thus modifying VEGF mRNA expression under hypoxia condition. Therefore, administration of high-dose TMP together with DHFR(DD)-Flt23k gene delivery may act synergistically to suppress VEGF at both the transcriptional level and the posttranslational level.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our in vitro study showed that a high dose of TMP could also inhibit VEGF mRNA expression (Figure S1). High doses of TMP can induce cell toxicity [20], thus modifying VEGF mRNA expression under hypoxia condition. Therefore, administration of high-dose TMP together with DHFR(DD)-Flt23k gene delivery may act synergistically to suppress VEGF at both the transcriptional level and the posttranslational level.…”
Section: Discussionmentioning
confidence: 99%
“…TMP treatment increased the frequency of micronuclei and sister chromatid exchanges (SCE) in human cells in vitro (10). Additionally, an increase in micronuclei frequency was observed using the cytokinesis-block micronucleus (CBMN) assay (11,12). By using the same technique, minor increases in micronuclei and SCE were found following SMX therapy.…”
Section: Trimethoprimmentioning
confidence: 97%
“…Trimethoprim is generally well-tolerated at the dosages used, and studies comparing trimethoprim to co-trimoxazole have shown that skin rashes and gastrointestinal upset are less common when trimethoprim is used alone. (14) An in vitro study revealed that trimethoprim and its conjugates exert a cytotoxic effect on cancer cells and induce cancer cell apoptosis (15). Furthermore, the trimethoprim structure exhibits structural similarity and common pharmacophoric features with colchicine and the combretastatins (Fig.…”
Section: Introductionmentioning
confidence: 99%